Synthesis, crystal structure, electric and magnetic properties of new UNiSi2 splat - Molčanová, Z.; Cieslar, M.; Havela, L.; Paukov, M.; Kavečanský, V.; Huráková, M.; Zentková, M.; Rajňák, M.; M. Mihalik Jr.,; Mihalik, M.; Milianchuk, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We explored the crystal structure, magnetic and transport properties of UNiSi2 material, which was prepared by rapid solidification — splat cooling. The UNiSi2 splat is mostly single phase, the refinement of crystal structure indicated orthorhombic CeNiSi2-type structure (space group Cmcm) with lattice parameters a = 4.0082 Å, b = 16.0813 Å and c = 4.0064 Å. Also SEM analysis revealed the morphology exhibiting dendritic grains in the matrix. TEM images indicate mixed structure formed by crystalline particles embedded into amorphous or nanocrystalline matrix. Magnetic and electrical properties of the splat resemble properties of samples, which were prepared by conventional methods, exhibiting a ferromagnetic transition at about 91 K and similar temperature dependence of resistivity. The coercive field of μ0Hc = 2.25 T is much enhanced due to the magnetic anisotropy introduced by the sample preparation technique. Barkhausen jumps were observed on the hysteresis loop. Magnetization of the sample does not saturate in magnetic fields up to μ0H = 18 T.